From Antigua to present day - Janine Ribeiro, Renato (2024)
In celebration of Ãlvaro Vasconcelos’80th birthday, the text addresses the long and fruitful path we have traveled since we met in Guatemala until the present day. A journey full of wholesome encounters and thought‘provoking reflections on the world.